New Trends in Machine Translation - Rico Pérez, Celia; de Santa Olalla Sánchez, Aurora (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThis article offers a general overview of current methods in corpus-based MT. It first presents corpus linguistics as the discipline from which new research methods have sprung up and deals with aspects such as corpus annotation and alignment. It introduces both example-based and statistics-based MT from a general perspective, and finally advocates these methods as a realistic approach to MT.